Role of Dashmool Tail Nasya and a combination of Herbo-Mineral Drugs in the management of Ardhavbhedak W.S.R. to Migraine- A Clinical Study: Effectiveness of Dashmool Tail Nasya and Herbo-Mineral Drugs in Managing Ardhavbhedak in Migraine Patients (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Headache is the most common health problem experienced by mankind in the presentscenario. There is a high percentage of people suffering from migraine of individuals worldwide.Migraine is usually a moderate or severe headache felt as a throbbing pain on one side of the head andmost of the time it includes nausea and vomiting along with increased sensitivity to light or sound,which resembles the classical symptoms of Ardhavbhedak which is one among the 11 types ofShirorogas as mentioned in Ayurvedicclassical texts.Acharya SushruthasquotedArdhavbhedakTridoshaj, Acharya Charak has mentioned it asVata Kaphajand AcharyaVagbhatthas considered itVataj. The present study deals with the enrolment of 12 patients as per theinclusion criteria of migraine who were treated with Dashmool Tail Nasya along with a combination ofShira Shooladi Vajra Rasa 250 mg, Laghu Soot Shekhar Rasa250 mg, and Godanti Bhasma500 mg BDwith honey for 30 days and were keenly assessed before treatment, after 15 days (follow-up) and afterthe treatment. Marked improvement was observed in most of the patients with subsidisation ofassociated symptoms as well.